Unravelling the misfit: How gender equity interventions in Nepal's agrobiodiversity management fails to respond to rapidly changing rural livelihood context - Bhattarai, Basundhara (Institute for Study and Development, 2019)
Presented by Basundhara Bhattarai (Institute for Study and Development), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.